Fenomenologia a projekt naturalizacji - Dan Zahavi (Avant, 2011)
[Phenomenology and the project of naturalization] In recent years more and more people have started talking about the necessity of reconciliating phenomenology with the project of naturalization. Is it possible to bridge the gap between phenomenological analyses and naturalistic models of consciousness? Is it possible to naturalize phenomenology? In their long introduction to the book Naturalizing Phenomenology published by Stanford University Press in 1999, the four co-editors, Jean Petitot, Francisco Varela, Bernard Pachoud, and Jean-Michel Roy set out to delineate what might be seen as a kind of manifesto for this new approach. An examination of this introduction is consequently a good starting point for a discussion of the issue.